Diperoxo Pertechnetic Acid Characterized by Spectroscopic and Quantum Chemical Studies. Issue 26 (19th July 2013) - Poineau, Frederic; Weck, Philippe F.; Burton‐Pye, Benjamin P.; Kim, Eunja; Francesconi, Lynn C.; Sattelberger, Alfred P.; German, Konstantin E.; Czerwinski, Kenneth R.
Abstract: The reaction of Tc(+7) with H2 O2 has been studied in HNO3 and the speciation of technetium was performed by UV/Vis spectroscopic analysis. UV/Vis measurements show that for HNO3 concentrations of more than 7M and H2 O2 concentrations of 4.25M, Tc(+7) reacts immediately and red solutions are obtained, whereas no reaction occurs at H2 O2 concentrations of 0.1M . The UV/Vis spectra of the red solutions exhibit a single band centered at 500 nm that is attributed to a Tc(+7) peroxo species. The nature of the Tc(+7) peroxo species was investigated by computational methods. The structures and electronic spectra of the putative species Tc(O2 )4 –, TcO(O2 )3 –, TcO3 (O2 ) –, TcO(O2 )2 (H2 O)(OH), and TcO2 (O2 )(H2 O)2 (OH) were studied by first principles methods. Calculations show these species to be stable; their calculated spectra were compared to the experimental spectrum and the results are consistent with the presence of diperoxo pertechnetic acid, i.e., TcO(O2 )2 (H2 O)(OH). Abstract : The speciation of Tc(+7) was performed in HNO3 /H2 O2 solutions by combined UV/Vis spectroscopic and quantum chemical calculations. Results are consistent with the presence of diperoxo pertechnetic acid.